Chemical thermodynamics, 4 : plenary lectures - Rouquerol, J. (Jean); Sabbah, Raphael (Pergamon Press, 1976)
Chemical Thermodynamics-4 presents the application of experimental methods of chemical thermodynamics. This book discusses the three properties of biological molecules, namely, colossal dimension, exclusive orderliness, and capability to be in different states or conformations depending on conditions. Organized into eight chapters, this book begins with an overview of the trends in thermochemistry that involve complex reaction systems and product mixtures. This text then discusses the problems relating to the standard state of solids and illustrates the utilization of enthalpy-of-mixing-data.